1998
DOI: 10.1159/000013336
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Initiation of Uremia Therapy and Survival in Patients with Progressive Renal Disease

Abstract: We conducted a prospective cohort study to detect any relationships between specific clinical features and laboratory indices at initiation of hemodialysis and long-term survival. One hundred and thirty-nine consecutive patients with chronic renal failure hospitalized to start maintenance hemodialysis between January 1990 and December 1994 were enrolled, and follow-up was completed through December 1995. At baseline, subjects were assigned to one of five groups based on their major indication for initiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Nephrologists initiate dialysis treatment in most cases on the basis of the observed evolution of uremic symptoms and laboratory investigations, such as plasma creatinine concentration and creatinine clearance [32]. However, the evolution of uremic symptoms varies from patient to patient [33], so there is substantial variation in timing of dialysis initiation [34][35][36]. The study by Obrador et al [36] revealed that there is wide variation in renal function at the initiation of dialysis in the US ESRD population, and a substantial fraction of patients (23%) start dialysis at levels of predicted glomerular filtration rate (GFR) !5 ml/ min.…”
Section: Pre-esrd Care Referral To the Nephrologist And Initiation Omentioning
confidence: 99%
“…Nephrologists initiate dialysis treatment in most cases on the basis of the observed evolution of uremic symptoms and laboratory investigations, such as plasma creatinine concentration and creatinine clearance [32]. However, the evolution of uremic symptoms varies from patient to patient [33], so there is substantial variation in timing of dialysis initiation [34][35][36]. The study by Obrador et al [36] revealed that there is wide variation in renal function at the initiation of dialysis in the US ESRD population, and a substantial fraction of patients (23%) start dialysis at levels of predicted glomerular filtration rate (GFR) !5 ml/ min.…”
Section: Pre-esrd Care Referral To the Nephrologist And Initiation Omentioning
confidence: 99%
“…Thus patients started earlier are liable to be those with more comorbid conditions, for example. One such analysis was reported by Ifudu et al [27] (fig. 9).…”
Section: Is Mortality On Dialysis Reduced By Starting Earlier?mentioning
confidence: 96%
“…No difference is seen (note that this was not a randomized study). Reprinted by permission from Ifudu et al [27].…”
Section: Can Protein Restriction Predialysis Safely Defer Dialysis?mentioning
confidence: 99%
“…Others and we have argued that the current practice of initiation of dialysis is flawed [1][2][3][4][5] and the study by Ifudu published last year supports this belief [51]. Based upon the similarity in the relationship of DPI to small solute clearances in predialysis patients and patients on continuous ambulatory peritoneal dialysis (CAPD) [33], the PD subcommittee of the NKF-DOQI suggested that adequacy targets for CAPD be used as the renal function at which dialysis should be instituted i.e., when the renal function declines to below a weekly renal Kt/V urea of 2.0 [9].…”
mentioning
confidence: 89%